Experimental Research on Nanotitanium-erythritol Energy Storage System - Zhang Xuelai; Ding Jinhong; Luo Xiaoxue; Xu Weiwen (Zhileng xuebao, 2016)
Erythritol with transformation temperature of 119 ℃ has huge potential in application according to temperature range of mobile heating, but it is also limited by its disadvantage of low thermal conductivity, unstable heat releasing, bigger supercooling. Nanometer materials as nucleating agents were putted into erythritol in order to improve its thermal properties, and the composite can be used as phase change materials (PCMs). The properties of nanotitanium-erythritol with different mass ratio have be gained by time-temperature curve, differential scanning calorimetry (DSC),thermal conductivity test and other properties testing. The results show that Nanometer materials can decrease the supercooling of erythritol in a large degree, and it can also increase its thermal conductivity in small extent; Nanometer titania can decrease the composite’s coefficient of cubical expansion, and the composite’s density will fluctuate over a little range with 0.02~0.08 g/cm3; Nanometer titania of 0.1% mass ratio has a drop of 37.91 percent in erythritol’s supecooling, 1.09 percent in its latent heat and a growth of 3.67 times in solid thermal conductivity.